Perceptions of Cultured Meat Among Youth and Messaging Strategies - Ruzgys, Shannon; Pickering, Gary J. (Frontiers in Sustainable Food Systems, 2020)
Cultured or ‘clean’ meat (CM) is arguably a more ethical and environmentally sustainable alternative to farmed meat, but several potential psychological barriers exist to its acceptance in the marketplace. The perceptions of youth, as a specific consumer cohort, have not been reported to date despite young adults having more flexible dietary habits and being more likely to avoid red meat because of animal welfare and environmental concerns. Thus, youth represent a demographic that may be more accepting of CM and for whom the pro-environmental consequences of early adoption may be realized across an entire lifespan. In this study of college-aged Canadians (mean=20 yrs), we examined perceptions of CM (mixed methods) and assessed the effects of educational messaging about its benefits and then naturalness framing on intention to consume it (within subjects quantitative experimental design). Results show that youth believe CM to be unnatural, ethical, and environmentally friendly, and that taste is an important element of acceptance. Linear regression showed that food disgust was a significant predictor for both intent to incorporate CM into regular diet and completely replace meat/meat substitutes with CM. In both instances, increasing food disgust was associated with lower behavioral intent. Environmental values were also a predictor for completely replacing meat/meat substitutes with CM, where it positively affected intent and showed a similar effect size to food disgust. Both messaging on the benefits of CM and naturalness framing increased intent to consume it across all three measures and by a similar magnitude (p(F)<0.05). These findings provide timely and actionable information for both CM producers and marketers and contribute to scholarship on the role of values and psychological traits in sustainable food choices.